2012
DOI: 10.1016/j.pmrj.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Daily Treatment Time and Functional Gains of Stroke Patients During Inpatient Rehabilitation

Abstract: The study demonstrated a significant relationship between daily therapeutic duration and functional gain during IRH stay and showed treatment time thresholds for optimal functional outcomes for patients in inpatient rehabilitation who had a stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 18 publications
1
47
1
4
Order By: Relevance
“…Evidence shows that early supported discharge services, similar to consultative and comprehensive rehabilitation in this study, can enhance the recovery of functional independence [38,39]. Linkages of prognosis to the type and intensity of rehabilitation services provided were consistent with reported findings in U.S. and Canadian stroke populations in a variety of settings [10,40,41]. Finally, our index emphasizes the importance of considering the effects of spontaneous recovery over time [42], allowing for adjustments for very short recovery windows, that is, 2 days or less versus 3 or more days between the initial and final functional assessments.…”
Section: Discussionsupporting
confidence: 82%
“…Evidence shows that early supported discharge services, similar to consultative and comprehensive rehabilitation in this study, can enhance the recovery of functional independence [38,39]. Linkages of prognosis to the type and intensity of rehabilitation services provided were consistent with reported findings in U.S. and Canadian stroke populations in a variety of settings [10,40,41]. Finally, our index emphasizes the importance of considering the effects of spontaneous recovery over time [42], allowing for adjustments for very short recovery windows, that is, 2 days or less versus 3 or more days between the initial and final functional assessments.…”
Section: Discussionsupporting
confidence: 82%
“…A retrospective cohort study of 360 subjects demonstrated that subjects who received >3.0 hours of therapy daily made significantly more functional gains than those receiving <3.0 hours daily, although hemorrhagic stroke, leftsided brain injury, earlier IRF admission, and longer IRF stay also were associated with total functional improvement. 60 Finally, the efficacy of complementary medicine techniques has been studied in the IRF environment. In a randomized, clinical trial of 274 subjects receiving acupuncture, PT, or both, no synergistic effect was found when acupuncture was added to PT, although all subjects exhibited functional gains.…”
Section: June 2016mentioning
confidence: 99%
“…Thirty minutes twice daily of supervised activity has been found to provide for gains in physical function and reduced length of stay in patients aged 65 years or older [42], yet three hours per day, five days a week has been found to provide such improvement in stroke patients [43]. A further, recent study of the time use of stroke patients undergoing rehabilitation in skilled nursing facilities indicated that therapeutic time use was significantly associated with an improved functional capability [35].…”
Section: Discussionmentioning
confidence: 99%